Ultra performance liquid chromatography mass spectrometry : evaluation and applications in food analysis - Naushad, Mu; Khan, Mohammad Rizwan (CRC Press, Taylor & Francis Group, 2014)
"This book presents a unique collection of up-to-date UPLC-MS/MS methods for the separation and quantitative determination of carbohydrates, lipids, proteins, peptides, amino acids, vitamins, aroma and flavor compounds in a wide variety of foods and food products. The book provides practical information to those who are involved in the research and development, production, or routing analysis of foods and food products"--
Keywords: analýza potravin; potravinářská aditiva; vysokoúčinná kapalinová chromatografie; hmotnostní spektrometrie; food analysis; food additives; high performance liquid chromatography; mass spectroscopy; kolektivní monografie; collective monographs